2014
DOI: 10.1016/j.sjpain.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged-release oxycodone/naloxone on pain control, bowel function and quality of life: A prospective observational study

Abstract: Background and aim Strong opioids including oxycodone are amongst the most effective analgesics to combat moderate to severe pain of various aetiologies, but opioid-induced bowel dysfunction (OIBD) represents a relevant problem. The rationale for development of a prolonged-release (PR) fixed combination of oxycodone and naloxone was to counteract OIBD. Due to its negligible oral bioavailability, the μ-opioid receptor antagonist naloxone is able to selectively displace opioids from local μ-receptors in the gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…29,33 Long-term evidence from 2 open-label studies of patients who were treated with oxycodone/naloxone for up to 52 weeks revealed relatively good safety and tolerability profiles with oxycodone/naloxone, and the reported AEs were found to be in line with those associated with opioid treatment. 20 In light of this, although withdrawals due to AEs were numerically higher in patients treated with oxycodone/naloxone than with tapentadol, oxycodone/naloxone is tolerable for a longer period of treatment. Oxycodone/naloxone therefore has proven tolerability in the long term and may offer benefits with respect to efficacy compared with tapentadol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,33 Long-term evidence from 2 open-label studies of patients who were treated with oxycodone/naloxone for up to 52 weeks revealed relatively good safety and tolerability profiles with oxycodone/naloxone, and the reported AEs were found to be in line with those associated with opioid treatment. 20 In light of this, although withdrawals due to AEs were numerically higher in patients treated with oxycodone/naloxone than with tapentadol, oxycodone/naloxone is tolerable for a longer period of treatment. Oxycodone/naloxone therefore has proven tolerability in the long term and may offer benefits with respect to efficacy compared with tapentadol.…”
Section: Discussionmentioning
confidence: 99%
“…In an observational study of 588 patients, treatment with oxycodone/naloxone led to statistically significant improvements in both bowel function and QoL compared with patients treated with other strong opioids (Po0.0001 for both outcomes). 20 The benefits of treatment with oxycodone/naloxone were found during a longer period in a 1-year open-label extension study, with a mean (SD) Bowel Function Index score that decreased from 35.6 (27.74) at the start of the extension study to a normal level (Bowel Function Index score r28.8) of 20.6 (24.01) after 1 year. 21,22 Another prescribed opioid analgesic for chronic pain is tapentadol † , although it has only recently become available for use in the treatment of chronic pain after receiving European Medicines Agency and Food and Drug Administration approval for use in this indication in 2011 and is not yet available in every country.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This analysis is based on the previously reported multicenter, prospective, observational study performed from 9 November 2009 through 15 December 2010 by German non-hospitalbased physicians [18]. The study was approved by an ethics committee and registered with the German Federal Institute for Drugs and Medical Devices (BfArM) with study code OXN9505.…”
Section: Methodsmentioning
confidence: 99%
“…Its analgesic effectiveness and the positive effects on bowel dysfunction under routine clinical practice conditions were demonstrated in a large prospective observational study involving 7836 patients with severe chronic pain of several etiologies [16] and in a retrospective observational study in cancer patients [17]. An additional prospective 4-to 6-week observational study in patients with moderate-to-severe pain of mostly musculoskeletal etiology showed a favorable outcome of OXN PR compared to other strong opioids in terms of pain control, bowel function and QoL measures [18]. In this study, 162 of 588 patients overall were opioid-naïve when treatment with OXN PR or other strong opioids was started.…”
Section: Introductionmentioning
confidence: 93%